Development of an Android-Based Ethnomathematics Module Using the Tri-N Model (Niteni, Nirokke, Nambahi) for Vocational School Trigonometry - Nayazik, Akhmad; Ramadhani, Lingga Kurnia; Fitriyani, Anggun (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
This study addresses gaps in vocational trigonometry learning by integrating ethnomathematics and Tri-N pedagogy into an Android-based module to enhance mathematical literacy and engagement. Research and Development (R&D) with a 4D model (Define, Design, Develop, Disseminate) was applied. Data were collected from expert validation sheets and student response questionnaires, and analyzed using descriptive and quantitative methods. The module achieved high validity (87.77%) and strong student acceptance (83.55%), indicating practicality and suitability for classroom use. The integration of Tri-N stages with ethnomathematical contexts and mobile technology supports active learning and cultural relevance, contributing theoretically to contextual mathematics education and practically to digital learning innovations. The developed module is valid and practical for vocational trigonometry instruction. Future research should explore scalability and effectiveness through broader trials. Keywords: Ethnomathematics, Tri-N Model, Android-Based Module, Vocational Education, Trigonometry